Prompt access to effective malaria treatment among children under five in sub-Saharan Africa: a multi-country analysis of national household survey data - Shah, Jui A. (Malar J, 2015)
BACKGROUND: Scaling up diagnostic testing and treatment is a key strategy to reduce the burden of malaria. Delays in accessing treatment can have fatal consequences; however, few studies have systematically assessed these delays among children under five years of age in malaria-endemic countries of sub-Saharan Africa. This study identifies predictors of prompt treatment with first-line artemisinin combination therapy (ACT) and describes profiles of children who received this recommended treatment. METHODS: This study uses data from the most recent Demographic and Health Survey, Malaria Indicator Survey, or Anaemia and Parasite Prevalence Survey conducted in 13 countries. A Chi square automatic interaction detector (CHAID) model was used to identify factors associated with prompt and effective treatment among children under five years of age. RESULTS: The percentage of children with fever who received any anti-malarial treatment varies from 3.6 % (95 % CI 2.8–4.4 %) in Ethiopia to 64.5 % (95 % CI 62.7–66.2 %) in Uganda. Among those who received prompt treatment with any anti-malarial medicine, the percentage who received ACT ranged from 32.2 % (95 % CI 26.1–38.4 %) in Zambia to nearly 100 % in Tanzania mainland and Zanzibar. The CHAID analysis revealed that country of residence is the best predictor of prompt and effective treatment (p < 0.001). Depending on the country, the second best predictor was maternal education (p = 0.004), place of residence (p = 0.008), or household wealth index (p < 0.001). CONCLUSIONS: This study reveals that country of residence, maternal education, place of residence, and socio-economic status are key predictors of prompt access to malaria treatment. Achieving universal coverage and the elimination agenda will require effective monitoring to detect disparities early and sustained investments in routine data collection and policy formulation.